Fabricating polymer-nanocomposite fiber for biomedical applications. - Chew, Shirlin. (2009)
Hydroxyapatite (HA) and Polyhedral oligomeric silsesquioxanes (POSS) have been used as biocompatible and osteoconductive substitutes in the biomedical field such as orthopedic. However, HA and POSS are difficult to shape in the specific forms required for bone substitution due to its hardness and brittleness. Therefore, novel composites of HA/Chitosan and POSS/Chitosan have became of great interests. The POSS used in this study is Aminopropylphenyl POSS (AM0273 POSS).